STUDI KARAKTERISTIK ALIRAN FLUIDA NON NEWTONIAN (PASIR BESI) - Yohana, Eflita (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2000)
This research investigated the characteristic of dilatant fluid flow of iron sand and water within a pipe.The fluid flow in a transparant pipe, a straight and an elbow pipe on horizontal position, with length 1.5 m for straight pipe and radius of curvature is 0.96 m for elbow pipe and 38 mm diameter. The variation of sand concentrations , were 4%, 6%, 9%, and 13%, for the elbow pipe and 4%, 5%, 7%, and 10%, for the straight pipe. The variation of flow rates within a range of 0.2 l/s to 2.5 l/s. The results show that rheology of dilatant fluid influenced by iron sand concentrations, flow rates and the forms of the pipe. Increasing the mass concentration will increased wall shear and fluid viscosity. The wall shear, the apparent viscosity and the friction coefficient on the elbow pipe are higher than straight pipe. At cm = 4 %, tw = 3,069 N/m2 ,hc = 0,012 N. s/m2, , cm = 13 %, tw = 3,999 N/m2, hc = 0,016 N. s/m2, for elbow pipe, and cm = 4 % , tw = 2,965 N/m2 ,hc = 0,010 N. s/m2, , cm = 7 %, tw = 2,755 N/m2 ,hc = 0,009 N. s/m2 , for the straight pipe. Key words : Fluid flow, Dilatant, Mass concentration, iron sand.